2021
DOI: 10.1159/000516630
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrates to Prevent and Treat Obesity in a Murine Model of Diet-Induced Obesity

Abstract: <b><i>Introduction:</i></b> The biggest risk factor for obesity and its associated comorbidities is a Western diet. This Western diet induces adipose tissue (AT) inflammation, which causes an AT dysfunction. Since AT is a vital endocrine organ, its dysfunction damages other organs, thus inducing a state of chronic inflammation and causing various comorbidities. Even though it is evident a Western diet, high in fat and carbohydrates, induces obesity and its complications, it is not known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
(56 reference statements)
1
2
0
Order By: Relevance
“…These findings suggested that sugar-enriched diet may have an inhibitory effect on hepatic primary bile acid synthesis in comparison to RG-enriched diet. However, the circulating cholesterol concentrations were not significantly different between these two diets, which have been consistent with some ,, but not all studies, , utilizing the isocaloric substitution model between sucrose and starch. The reason for the discordant results between ours and previous studies may be attributed, in part, to the different sugar compositions.…”
Section: Discussionsupporting
confidence: 89%
“…These findings suggested that sugar-enriched diet may have an inhibitory effect on hepatic primary bile acid synthesis in comparison to RG-enriched diet. However, the circulating cholesterol concentrations were not significantly different between these two diets, which have been consistent with some ,, but not all studies, , utilizing the isocaloric substitution model between sucrose and starch. The reason for the discordant results between ours and previous studies may be attributed, in part, to the different sugar compositions.…”
Section: Discussionsupporting
confidence: 89%
“…Herein, we demonstrate that the administration of a standard chow diet ad libitum for only 2 weeks after 6 weeks of HF diet exposure normalizes BW, adiposity, glucose and cholesterol levels, and glucose tolerance. Intriguingly, a recent study performed in a murine model of diet‐induced obesity supports that switching to a sucrose‐rich diet after western diet intake elicits weight loss and decreases obesity‐induced metabolic complications and points out the potential of carbohydrates to treat obesity 29 . However, we have recently evidenced that the nature of the carbohydrates and lipids included in the diet, and not only the amount of these macronutrients, is crucial to maintain cardiometabolic health 4 .…”
Section: Discussionmentioning
confidence: 86%
“…Intriguingly, a recent study performed in a murine model of diet-induced obesity supports that switching to a sucrose-rich diet after western diet intake elicits weight loss and decreases obesity-induced metabolic complications and points out the potential of carbohydrates to treat obesity. 29 However, we have recently evidenced that the nature of the carbohydrates and lipids included in the diet, and not only the amount of these macronutrients, is crucial to maintain cardiometabolic health. 4 These results are aligned with the 2019 Position Statement from the American College of Cardiology/American Heart Association (ACC/AHA) and the European Society of Cardiology/European Atherosclerosis Society (ESC/EAS) supporting healthy dietary patterns and includes the following recommendations: increased consumption of fiber-rich complex carbohydrates but limited intake of less healthy carbohydrate-rich foods, such as refined starches or sugars, a reduced consumption of saturated fat and a moderate intake of MUFA and PUFA, together with lowsalt and moderate alcohol consumption, and the promotion of physical exercise.…”
Section: Discussionmentioning
confidence: 99%